2020
DOI: 10.3390/insects11090607
|View full text |Cite
|
Sign up to set email alerts
|

Biology and Prevalence in Northern Italy of Verrallia aucta (Diptera, Pipunculidae), a Parasitoid of Philaenus spumarius (Hemiptera, Aphrophoridae), the Main Vector of Xylella fastidiosa in Europe

Abstract: The meadow spittlebug, Philaenus spumarius (L.) (Hemiptera Aphrophoridae), the main vector of Xylella fastidiosa Wells et al. in Europe, has few known natural enemies. The endoparasitoid Verrallia aucta (Fallén) (Diptera, Pipunculidae) was first noticed a long time ago but very little is known about its biology and prevalence. In this study, the presence and prevalence of V. aucta were investigated in different regions of northern Italy, both in plain–foothill and montane zones. Parasitic larvae were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 31 publications
5
34
1
Order By: Relevance
“…Of particular interest was the signal of the specialized dipteran parasitoid, V. aucta , in 24.7% of P. spumarius individuals studied. This ratio is comparable to the 17.5% infection prevalence estimates for P. spumarius populations from the northern Italy (Molinatto et al ., 2020), using diagnostic PCR reactions. Then, the COI amplicon sequencing-based screens of individual insects, besides confirming their identity, can provide believable information on some of their biotic associations.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Of particular interest was the signal of the specialized dipteran parasitoid, V. aucta , in 24.7% of P. spumarius individuals studied. This ratio is comparable to the 17.5% infection prevalence estimates for P. spumarius populations from the northern Italy (Molinatto et al ., 2020), using diagnostic PCR reactions. Then, the COI amplicon sequencing-based screens of individual insects, besides confirming their identity, can provide believable information on some of their biotic associations.…”
Section: Discussionsupporting
confidence: 87%
“…Of particular interest was the signal of the specialized dipteran parasitoid, V. aucta, in 24.7% of P. spumarius individuals studied. This ratio is comparable to the 17.5% infection prevalence estimates for P. spumarius populations from the northern Italy (Molinatto et al, 2020), using diagnostic PCR reactions.…”
Section: Coi Amplicon Data As the Essential Framework For The Microbi...supporting
confidence: 82%
“…The predation dynamics of the generalist predator Zelus renardii Kolenati on P. spumarius were reported by Liccardo et al [ 96 ]. Furthermore, Molinatto et al [ 97 ] reported the infestation of field-collected spittlebugs by the parasitoid fly Verrallia aucta Fallén. Data for these natural enemy–vector interactions are preliminary and additional studies are needed to fully understand the degree of parasitoid–prey specificity to avoid non-target effects associated with any augmentative biocontrol measure.…”
Section: Current Attempts To Control the Insect Vector(s) In Olives—state Of The Artmentioning
confidence: 99%
“…the main driver of X. fastidiosa secondary spread within Apulian olive orchards (Cornara et al 2017b(Cornara et al , 2019EFSA et al 2019). Extensive soil tilling, particularly in dry environments, such as Mediterranean olive orchards, may affect soil quality negatively, augment the risk of desertification, and reduce habitats sheltering beneficial arthropods, i.e., predators, parasitoids, and pollinators (Bodino et al 2020;Kairis et al 2013;Karamaouna et al 2019;Mesmin et al 2020;Molinatto et al 2020). Pesticides, on the other side, are not often compatible with integrated pest management techniques and have been listed among the main drivers of terrestrial biodiversity decline (Desneux et al 2007;Brühl & Zaller 2019;Chávez-Dulanto et al 2021;Sánchez-Bayo & Wyckhuys 2019).…”
Section: Introductionmentioning
confidence: 99%